Problems of physical education students in making a kinesiological diagnosis of swimmers - Persyn, U.; Colman, V. (Biomechanics and Medicine in Swimming VIII, 1999)
To analyse styles of average swimmers causing low back pain, two style variants at international level were chosen as a reference. Problem phases in the stroke cycle were specified and implemented in a computer aided instruction program (CAI). The CAI-program was used to study the capacity of future Physical Education (PE) teachers in making a kinesiological diagnosis. This included the observation of the movement and the interpretation of stroke mechanics and of anatomical implications. The problem was not the observation of the global stroke cycle, but the observation and the interpretation of faulty phases. To improve the capacity to diagnose, pedagogical tools, such as a water visualisation method in addition to CAI, are recommended to be utilised.